In vitro and in vivo studies of antimicrobial peptide B1CTcu5 analogs encapsulated in colon-specific microparticles against Mycobacterium tuberculosis - Roque Borda, Cesar Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Tuberculosis (TB) remains one of the major global public health challenges, exacerbated by the emergence of drug-resistant strains of Mycobacterium tuberculosis (MTB). In this context, the overall objective of this thesis was the development, characterization, and application of antimicrobial peptides and advanced drug delivery systems as alternative and complementary strategies for the treatment of tuberculosis and associated bacterial infections. Chapter 1 presents the general considerations of the thesis, including the problem background, the objectives of the study, and a critical review of the literature, addressing the limitations of conventional therapies, the potential of antimicrobial peptides, and the role of delivery systems in enhancing therapeutic efficacy and selectivity. Chapter 2 describes the discovery and rational design of antimicrobial peptides with antitubercular activity. A library of peptide analogues was generated through iterative batch synthesis, leading to the identification of the peptide CR22DK-S18G, which exhibited a minimum inhibitory concentration (MIC) of 1.2 µg/mL against Mycobacterium tuberculosis, with high selectivity and low cytotoxicity. This chapter comprehensively addresses peptide synthesis, biological evaluation, selectivity studies, mechanisms of action, and immune response modulation. Chapter 3 is dedicated to the investigation of antimicrobial peptide interactions with the mycobacterial membrane. In silico approaches, including molecular docking and molecular dynamics simulations, were integrated with experimental assays, enabling the elucidation of peptide interactions with mycolic acid-rich membranes and the correlation of these interactions with the observed antimicrobial activity. Chapter 4 explores colon-targeted delivery systems based on alginate microparticles with a double coating of chitosan and HPMCAS, loaded with antimicrobial peptides. The results demonstrate peptide protection throughout the gastrointestinal tract and efficacy in preventing intestinal infections, highlighting the potential of these formulations for site-specific applications in the enteric environment. Chapter 5 addresses self-assembly-based delivery systems, employing alginate–pectin microparticles embedding self-associated antimicrobial peptides and resveratrol. This chapter demonstrates the development of systems with combined antimicrobial and anti-inflammatory activity, underscoring the relevance of peptide self-assembly for multifunctional therapeutic applications. Chapter 6 presents nanotechnological applications of antimicrobial peptides against Mycobacterium tuberculosis, focusing on N-acetylcysteine-modified chitosan nanoparticles functionalized with peptides. The developed formulations were able to potentiate drug activity against clinical MTB isolates, demonstrating synergistic effects and translational relevance. Finally, Chapter 7 brings together the general perspectives and conclusions of the thesis, integrating the main findings and discussing the potential of antimicrobial peptides combined with advanced drug delivery systems as promising therapeutic platforms. Overall, this thesis establishes solid foundations for the future development of multifunctional peptide conjugates and rational strategies aimed at combating tuberculosis and drug-resistant bacterial infections.

A tuberculose (TB) permanece como um dos principais desafios de saúde pública global, agravado pela emergência de cepas de Mycobacterium tuberculosis (MTB) resistentes aos fármacos disponíveis. Diante desse cenário, esta tese teve como objetivo geral o desenvolvimento, a caracterização e a aplicação de peptídeos antimicrobianos e sistemas avançados de liberação de fármacos como estratégias alternativas e complementares no combate à tuberculose e a infecções bacterianas associadas. O Capítulo 1 apresenta as considerações gerais da tese, incluindo a contextualização do problema, os objetivos do trabalho e uma revisão crítica da literatura, abordando os limites das terapias convencionais, o potencial dos peptídeos antimicrobianos e o papel de sistemas de liberação no aumento da eficácia e seletividade terapêutica. O Capítulo 2 descreve a etapa de descoberta e desenho racional de peptídeos antimicrobianos com atividade antituberculosa. Uma biblioteca de análogos peptídicos foi gerada por síntese iterativa em bateladas, resultando na identificação do peptídeo CR22DK-S18G, que apresentou concentração inibitória mínima (CIM) de 1,2 µg/mL contra Mycobacterium tuberculosis, com seletividade elevada e baixa citotoxicidade. O capítulo aborda de forma abrangente a síntese peptídica, a avaliação biológica, estudos de seletividade, mecanismos de ação e modulação da resposta imune. O Capítulo 3 é dedicado à investigação das interações dos peptídeos antimicrobianos com a membrana micobacteriana. Foram integradas abordagens in silico, incluindo docking molecular e simulações de dinâmica molecular, com ensaios experimentais, permitindo compreender a interação dos peptídeos com membranas ricas em ácidos micólicos e correlacionar esses dados com a atividade antimicrobiana observada. O Capítulo 4 explora o uso de sistemas de liberação direcionados ao cólon, baseados em micropartículas de alginato com dupla cobertura de quitosana e HPMCAS, carregadas com peptídeos antimicrobianos. Os resultados demonstram proteção do peptídeo ao longo do trato gastrointestinal e eficácia na prevenção de infecções intestinais, destacando o potencial dessas formulações para aplicações específicas no ambiente entérico. O Capítulo 5 aborda sistemas de liberação baseados em auto-organização, utilizando micropartículas de alginato-pectina contendo peptídeos antimicrobianos autoassociados e resveratrol. Este capítulo demonstra a obtenção de sistemas com atividade antimicrobiana e anti-inflamatória combinada, evidenciando a relevância da auto-montagem peptídica para aplicações terapêuticas multifuncionais. O Capítulo 6 apresenta aplicações nanotecnológicas de peptídeos antimicrobianos contra Mycobacterium tuberculosis, com foco em nanopartículas de quitosana modificadas com N-acetilcisteína funcionalizadas com peptídeos. As formulações desenvolvidas foram capazes de potencializar a atividade de fármacos contra isolados clínicos de MTB, demonstrando sinergismo e relevância translacional. Por fim, o Capítulo 7 reúne as perspectivas e conclusões gerais da tese, integrando os principais achados e discutindo o potencial dos peptídeos antimicrobianos associados a sistemas avançados de liberação de fármacos como plataformas terapêuticas promissoras. A tese estabelece bases sólidas para o desenvolvimento futuro de conjugados peptídicos multifuncionais e estratégias racionais voltadas ao enfrentamento da tuberculose e de infecções bacterianas resistentes.
Estudos in vitro e in vivo de análogos do peptídeo antimicrobiano B1CTcu5 encapsulados em micropartículas colón-específicas frente ao Mycobacterium tuberculosis
Keywords: peptide antibiotics; controlled release preparations; drug discovery; tuberculosis; drug delivery systems